COVID-19 in Turkey: Lessons Learned - Banu Cakir (Springer, 2020)
Turkey reported its first COVID-19 case on March 10, 2020. We present here the mitigation efforts Turkey has undertaken so far, and also review the lessons learned for future proactive strategies. High number of intensive care unit beds and ventilators, national treatment algorithms, governmental support for free testing and medications, tedious contact-tracing with early detection and isolation of cases together with early shelter-in-place for the elderly and youngsters, and subsequent weekend curfews in selected cities have so far prevented the surge pressure on the health care system. At this phase, Turkey needs to adopt an evidence-based, proactive control system for an effective transition process to normalize the situation. Here, we underline the urgent need for detailed analysis of the national COVID-19 data and propose an epidemiologic investigation framework for better understanding, efficient control, and reliable forecasting of COVID-19 pandemic.